Evaluasi Pemutahiran Daftar Pemilih Berkelanjutan diKomisi Pemilihan Umum Kabupaten Ogan Komering Ilir - Hasibuan, Sry Sudarwaty; Idris, Umiyati; Berlian, Ong (@-Publik: Jurnal Administrasi Publik, 2021)
This study aims to evaluate the continuous voter list update at General Election Commission of Ogan Komering Ilir Regency. This research uses qualitative method to describe the implemen-tation of continuous voter list update at General Election Commission of Ogan Komering Ilir Re-gency.This studyshows that the continuous voter list update at General Election Commission of Ogan Komering Ilir Regency hasn’t been implemented optimally. Continuous voter list monitor-ing has been implemented optimally, but the fund allocated for this program is not enough due to some of the amount being reallocated for COVID-19 pandemic handling. The number of human resources involved in this program is also not optimal because there is only one operator that ad-minister voters list in 18 districts in Ogan Komering Ilir Regency. There are two factors that causes difficulties in obtaining voters’ data: (1) the data obtained from the funeral service is not valid due to not all of the people being buried within the area of Ogan Komering Ilir Regency are of Ogan Komering Ilir Residents; and (2) The large number of people not issuing death certificate of the member of their family who has passed, which means there are people who has passed that are still registered as voters.